Conventionalised impoliteness towards perceived ESL users on an anonymous imageboard / Mohamad Ammar Rosli - Mohamad Ammar , Rosli (2019)
On 4chan, an anonymous imageboard, certain users are labelled as ‘ESL’ even though there are no information regarding their ethnicity, nationality, or languages spoken. Perceived ESL users on the website are often insulted, harassed, and ostracized by other users. To further understand this phenomenon, 1000 posts and 10 discussion threads containing the term ‘ESL’ are extracted from a third party archive of the website as data. To analyse the data, the conventionalised impoliteness formulae by Culpeper (2011) are used. The data analysis reveals that the impoliteness towards perceived ESL users are triggered by agrammatical posts and perceived ESL users are often stereotyped as being less intelligent compared to native speakers of English. In addition, the racial slurs found in the data also suggest that there seems to be a relationship between being perceived as ESL and being perceived as a minority on the website.